Reduction mechanism of hydrothermally synthesized wide band gap ZnWO4 nanorods for HER application - Shreya; Phogat Peeyush; Singh Sukhvir; Jha Ranjana (MATEC Web of Conferences, 2024)
This manuscript presents a detailed investigation of the synthesis of zinc tungstate (ZnWO4) nanoparticles and various characterizations of the as-synthesized sample to reveal its potential for hydrogen evolution reaction (HER). The study focuses on a simple and efficient hydrothermal method that facilitates the production of ZnWO4 nanoparticles, which involves the controlled reaction between zinc and tungstate ions in a specific solution. The resulting ZnWO4 nanoparticles were characterized by various characterization techniques which include XRD, UV-vis spectroscopy, TEM and electrochemical study to get insights into their size, structure, properties and electrochemical behaviour. The characterization includes the analysis of the nanoparticles' structural features and optical properties. The material’s electrochemical properties were also investigated by employing cyclic voltammetry (CV) and potentio electrochemical impedance spectroscopy (PEIS). The charge transfer process was studied for the material revealing its diffusion controlled behaviour and reduction peaks in the cathodic region. These properties suggest that the material is a potential candidate for HER catalysis.